Una articulación metodológica: desde textos del Socio-analisis, I(A)P, F. Praxis, Evelyn F. Keller, Boaventura S. Santos, etc. - Villasante, Tomás R. (Política y Sociedad, 2007)
This text makes a review, following the contributions of the last decades, from different theoretical currents and practices that make the bases for participative methodologies. It revise texts from socioanalytic, participative investigation action, philosophy of praxis, a debate between constructionisms, aportations from ecofeminism, from ecology of knowledge, etc. and articulate many of this positions in a explicative diagram (of 12 positions) who try to make a differentiation and relation between practice and theory proposition showed in this pages.